COMPARATIVE ANALYSIS AND ADAPTATION FRAMEWORK FOR INTERNATIONAL WARRANTY STANDARDS TO U.S. COMMERCIAL REQUIREMENTS: MITIGATING FINANCIAL RISKS IN THE SUPPLY OF HEAVY-DUTY COMPONENTS - Kapeliukh, O. V. (Global Prosperity, 2026)
This study integrates a comparative legal analysis of EU and US statutes with supply chain gap analysis to identify critical bottlenecks in cross-border warranty processing, regarding reverse logistics, labor cost inflation and defect verification latency. The analysis reveals that traditional parts-only reimbursement models are commercially unviable within the US market. To address this, the article proposes a hybrid alignment strategy - a methodological framework that harmonizes European operational prudence with American commercial demands. Key components include the implementation of capped labor reimbursement models based on standard repair times, the adoption of scrap-in-field protocols for low-value components and the deployment of a centralized digital ecosystem for evidence-based adjudication. The implementation of these standardized protocols transforms warranty management from an unpredictable cost center into a strategic instrument for financial hedging. By automating claim triage and enforcing objective verification standards, suppliers can optimize working capital, mitigate fraud risks and secure a competitive advantage in the transatlantic supply chain.